Integrating Duolingo in EFL Classrooms: A Gamified Approach to Strengthening Vocabulary and Reading Competence - Pratama, Bima Samudra Aji; Lolita, Yuri (JET ADI BUANA, 2025)
This study investigates the impact of gamified learning through Duolingo on the vocabulary mastery of EFL students and its subsequent effect on reading Skill. Grounded in theories of gamification, self-regulated learning (SRL), and the Octalysis Framework, the research employed a quasi-experimental design involving 62 eleventh-grade students at one Senior High School at Mojokerto, East Java, divided into an experimental group using Duolingo and a control group taught with conventional methods. A vocabulary test consisting of 25 items across five reading-based indicators was administered as both pre-test and post-test. Several statistics step were applied to analyze the data. Further analysis across five indicators revealed that the most notable gains were in students' ability to recognize word meanings in context and apply vocabulary in varied reading tasks. These findings highlight the pedagogical value of Duolingo in improving not only vocabulary acquisition but also its application in reading skill. Gamified language learning platforms are thus recommended as effective tools to support vocabulary development in EFL contexts.